The Impact of Principal Academic Supervision on Teacher Professionalism - Putri, Rika Dwi; YAOU, Tamégnon; Nitiasih, Putu Kerti; Asvio, Nova (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2022)
This study investigated the influence of academic supervision by the principal in improving the professionalism of TK Negeri Pembina North Indralaya teachers. The administrators and instructors provided data for this study. Data collecting methods include 1) interviews, 2) observation, and 3) documentation. Techniques for analyzing data include 1) data reduction; 2) data display; and 3) conclusion. The results obtained indicate that principals serve as educators, managers, administrators, supervisors, leaders, innovators, and motivators in increasing the professionalism of North Indralaya State Kindergarten teachers. This study is still in its early stages since it attempts to examine in depth the growth of teacher professionalism connected with the principal's academic supervision. This study contributes to school principals, who will increase teacher professionalism by expanding the role of academic monitoring.